2021
DOI: 10.1136/bmjopen-2020-042654
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mortality and leading causes of deaths: a descriptive study in China, 2014–2018

Abstract: ObjectiveThe present study estimated the national and urban–rural levels and causes of neonatal deaths in China annually between 2014 and 2018 to provide data support for the further end of preventable neonatal deaths for China and other low-income and middle-income countries.MethodsThe study was based on data from the National Maternal and Child Health Surveillance System. All neonates of surveillance districts (gestational week: ≥28 weeks) who died after delivery have been involved in the study. The mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
23
1
2
Order By: Relevance
“…Moreover, preterm birth is the most common cause of neonatal death. 49 From the perspectives of society and family loss, the burden of preterm birth in China is substantial. The Chinese Government's strategic investments in maternal and neonatal health have partly contributed to the prevention of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preterm birth is the most common cause of neonatal death. 49 From the perspectives of society and family loss, the burden of preterm birth in China is substantial. The Chinese Government's strategic investments in maternal and neonatal health have partly contributed to the prevention of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Baroni et al [ 7 ] investigated the neonatal mortality rates in Brazil, whereas Liu et al [ 8 ] and Abdul-Mumin et al [ 9 ] investigated the key reasons for neonatal death and preterm birth in China and Ghana. Regional investigations have identified that preterm birth, intrapartum complications and pneumonia (in case of China), and preterm birth complications and birth asphyxia (in case of Ghana) are the leading causes of neonatal deaths [ 8 , 9 ]. On a global scale, the major causes of neonatal death include preterm birth, severe infections and asphyxia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have mostly considered a single outcome variable; in some cases, two variables were considered to examine the association between maternal obesity with other variables of interest, including miscarriage, stillbirth [ 4 ] and neonatal death [ 8 , 9 ]. In contrast, this research has taken a holistic approach to compare and contrast how maternal obesity is related to pre and post-birth maternal and neonatal risk factors by including multiple outcome variables together.…”
Section: Introductionmentioning
confidence: 99%
“…We found that preterm infants admitted to NICUs in eastern China were at the lowest risks of death, whereas infants in western China had the highest mortality. Several studies have reported a similar disparity of maternal, child, and neonatal mortality from eastern to western China (1)(2)(3)(20)(21)(22)(23). Overall, inadequate health service infrastructures and low health expenditure due to less developed economic status are thought to have resulted in inequity in neonatal and child health in the western region (2,23).…”
Section: Discussionmentioning
confidence: 98%